ROLE OF NARRATIVES IN FINANCIAL DECISION MAKING FROM PERSPECTIVE OF EMOTIONAL FINANCE - Dumanli, Asiye Nur; Aren, Selim (FUTURE ACAD, 2019)
In this study, the narratives, one of the important building blocks of emotional finance, is discussed. Emotional finance examines the role of unconscious mental processes in financial decision making on the basis of psychoanalysis. It uses concepts such as narrative, group feel, states of mind and phantasy in order to explain the behavior of investors in a market dominated by uncertainty Emotional finance has increasingly been discussed especially in the aftermath of the 2008 crisis. In these studies, the crisis periods and the formation of asset price bubbles, all which the conventional finance theory had difficulty in explaining, have been handled through the group feel, narratives, states of mind and phantasy concepts. Through this study, the effect of narratives over financial decision making is considered from the perspective of emotional finance Moreover, the role of narratives in the periods of asset price bubbles and financial crisis is explained. Narratives play a critical role in enabling individuals who must make decisions under uncertainty to imagine the future and to act. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Emotional finance; narratives; asset price bubbles; financial crisis; PHANTASTIC OBJECTS; SENSE; RISK; Business & Economics